KEDUDUKAN PEMIKIRAN KI HADJAR DEWANTARA DALAM FILSAFAT PENDIDIKAN - Siswadi, Gede Agus; Murtiningsih, Rr. Siti (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Ki Hadjar Dewantara is a central figure in education in Indonesia. His various thoughts were able to provide awareness to society during the Dutch colonial era, which did focus on education that was more oriented toward work skills. Ki Hadjar Dewantara through his great determination to establish an educational institution named